2016
DOI: 10.1007/s00122-016-2806-z
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping for downy mildew resistance in cucumber via bulked segregant analysis using next-generation sequencing and conventional methods

Abstract: QTL mapping using NGS-assisted BSA was successfully applied to an F population for downy mildew resistance in cucumber. QTLs detected by NGS-assisted BSA were confirmed by conventional QTL analysis. Downy mildew (DM), caused by Pseudoperonospora cubensis, is one of the most destructive foliar diseases in cucumber. QTL mapping is a fundamental approach for understanding the genetic inheritance of DM resistance in cucumber. Recently, many studies have reported that a combination of bulked segregant analysis (BSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(34 citation statements)
references
References 46 publications
0
34
0
Order By: Relevance
“…Four QTLs (dm2.1, dm4.1, dm5.1, and dm6.1) were detected by the cross between DM-resistant inbred line WI7120 and susceptible '9930', and dm4.1 and dm5.1 were major effect QTLs [13]. Five QTLs (dm2.2, dm4.1, dm5.1, dm5.2, and dm6.1) were found using NGSassisted BSA, and dm2.2 and dm5.2 were major effect loci for DM resistance [14]. reported that dm5.1, dm5.2, and dm5.3 were major-effect QTLs contributing to DM resistance.…”
Section: Downy Mildew (Dm) Is Caused By the Obligate Biotrophic Oomycmentioning
confidence: 98%
“…Four QTLs (dm2.1, dm4.1, dm5.1, and dm6.1) were detected by the cross between DM-resistant inbred line WI7120 and susceptible '9930', and dm4.1 and dm5.1 were major effect QTLs [13]. Five QTLs (dm2.2, dm4.1, dm5.1, dm5.2, and dm6.1) were found using NGSassisted BSA, and dm2.2 and dm5.2 were major effect loci for DM resistance [14]. reported that dm5.1, dm5.2, and dm5.3 were major-effect QTLs contributing to DM resistance.…”
Section: Downy Mildew (Dm) Is Caused By the Obligate Biotrophic Oomycmentioning
confidence: 98%
“…Combining the BSA strategy with a high-throughput NGS technology is a common practice for gene identification and QTL mapping. Many studies have outlined methodologies and applications of high-throughput sequencing in BSA for qualitative and quantitative traits (Abe et al, 2012; Takagi et al, 2013; Win et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…In plant breeding research, the main pipeline used for BSA, termed QTL‐seq, was developed by Takagi et al (2013) and has been widely used in several crops for many traits (e.g., Das et al, 2014; Lu et al, 2014; Win et al, 2016; and many others). Takagi and colleagues define the ∆(SNP‐index) for each SNP as the difference of the low value bulk SNP‐index from the high value bulk SNP‐index.…”
mentioning
confidence: 99%